Gestión empresarial y la calidad del servicio en supermercado Álamo - Sucursal San Francisco de la ciudad de Riobamba. - Muñoz Machado, Edgar Marcelo (2026)
The objective of this research is to determine how business management influences the quality of service at the Álamo–San Francisco supermarket branch, located in the city of Riobamba. The study responds to the need to strengthen the establishment’s internal organization and improve the customer experience in an increasingly competitive commercial environment. Using a hypothetical–deductive method with a descriptive–correlational approach, surveys were administered to supermarket customers to examine their perceptions of key aspects such as customer service, product supply, cleanliness, and responses to inconveniences. The results show that, although there is a positive evaluation of elements such as schedule compliance and product quality, weaknesses persist in staff supervision, complaint resolution, and internal communication. From a theoretical perspective, business management models and service quality models were addressed as essential tools for optimizing processes and improving customer satisfaction. Based on the analysis carried out, strategies focused on continuous improvement were proposed, including the implementation of service protocols, ongoing staff training, visible supervision, the use of basic digital tools, and a strengthened service-oriented approach. Finally, it is reaffirmed that efficient business management not only impacts the internal organization of the supermarket but is also key to ensuring comprehensive service, building consumer confidence, and strengthening customer loyalty. The application of these strategies will raise the quality of service and position the supermarket as a benchmark for customer service within the local market.